Words most often misspelled and mispronounced - Gallagher, Ruth Gleeson; Colvin, James (New York : Pocket Books, 1963)
A basic reference guide to the 23,000 trickiest words in the English language. Specially designed to provide quick answers to the correct spelling and pronunciation of the words most likely to be looked up by office workers, speakers, writers, and students.
Keywords: English language -- Pronunciation; English Language--Orthography and Spelling; English Language--Pronunciation.